DESIGN AND CONSTRUCTION OF A COMPUTER CONTROLLED AUTOMATIC SEQUENTIAL RAIN SAMPLER - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2013)
The preliminary goal of this study was to design, construct and apply a new automatic sequential precipitation sampling instrument. The proposed sequential sub-event sampler was designed in two sections: mechanical and electronical sections. The mechanical part includes a series of 100 mL sampling bottles on it, and a metallic body. The electronic part is composed of digital and analog sensors, various electronic material and a computer as the main controller of the system. Commands generated by the computer control the system, and the sub-event sampling period and the volume can be adjusted. Besides the volume and time controlled sampling, intelligent control and sampling is possible by developing adequate algorithms. Since the system consists of automatic sensors that can be controlled by the computer, anthropogenic errors in sampling are expected to be kept at minimum. The proposed instrument is open to development and additions can be easily made. The application phase includes collection of sequential precipitation samples, their analysis and an attempt to determine the sources of environmental pollution. The developed equipment was used to collect samples for five rain events that took place on 7 September 2007. The samples were analyzed for Na+, Mg2+, Ca2+ and K+ to obtain the temporal variation of the chemical composition during the precipitation event.
Keywords: precipitation; sequential rain sampling; rain chemistry; ion concentrations; PRECIPITATION; DEPOSITION; ELEMENTS